Mesozooplankton assemblages in two bays in the Beagle Channel (Argentina) during January, 2001 ... : تتجمع العوالق الوسيطة في خليجين في قناة بيجل (الأرجنتين) خلال يناير 2001 ... - Melisa Daiana Fernández-Severini; Mónica S. Hoffmeyer (OpenAlex, 2005)
This paper describes the composition and abundance of mesozooplankton of Bahía Ushuaia and Bahía Golondrina.These small bays are located in the northern Beagle Channel.Sampling was carried out from January 20 to 23, 2001 and samples were collected from the upper layer at nine stations.This study is the first research on mesozooplankton in this part of the Beagle Channel.Due to their dominance in the mesozooplankton community, we compared our Copepoda data with those reported by other authors from Antarctic coastal environments.By applying cluster analysis, we found two station groups in both bays: one in slightly polluted zones and the other in undisturbed external zones.Four assemblages in Bahía Ushuaia and two in Bahía Golondrina were determined by using non-metric multidimensional scaling (MDS) and cluster analysis.Mesozooplanktonic assemblages showed a certain resemblance in zones with and without anthropogenic influence.Most of the copepod species in our samples are typical of the sub-Antarctic ... : تصف هذه الورقة تكوين ووفرة العوالق الحيوانية المتوسطة في باهيا أشوايا وباهيا غولوندرينا. تقع هذه الخلجان الصغيرة في قناة بيغل الشمالية. تم إجراء أخذ العينات في الفترة من 20 إلى 23 يناير 2001 وتم جمع العينات من الطبقة العليا في تسع محطات. هذه الدراسة هي أول بحث حول العوالق الحيوانية المتوسطة في هذا الجزء من قناة بيغل. نظرًا لهيمنتها في مجتمع العوالق الحيوانية المتوسطة، قارنا بيانات الكوبيبودا الخاصة بنا مع تلك التي أبلغ عنها مؤلفون آخرون من البيئات الساحلية في القارة القطبية الجنوبية. من خلال تطبيق التحليل العنقودي، وجدنا اثنين مجموعات المحطات في كلا الخلجان: واحدة في مناطق ملوثة قليلاً والأخرى في مناطق خارجية غير مضطربة. تم تحديد أربع تجمعات في باهيا أوشوايا واثنتين في باهيا غولوندرينا باستخدام التحجيم متعدد الأبعاد غير المتري (MDS) وتحليل المجموعات العنقودية. أظهرت التجمعات العوالق الحيوانية المتوسطة تشابهًا معينًا في المناطق ذات التأثير البشري المنشأ أو بدونه. معظم أنواع مجدافيات الأرجل في عيناتنا نموذجية في منطقة أنتاركتيكا الفرعية. تُظهر أويثونا سيميليز (= O.helgolandica sensu Ramírez، 1966)، و Oncaea ...